2010
DOI: 10.1007/s00251-009-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MHC class I genes across horse MHC haplotypes

Abstract: The genomic sequences of 15 horse Major Histocompatibility Complex (MHC) class I genes and a collection of MHC class I homozygous horses of five different haplotypes were used to investigate the genomic structure and polymorphism of the equine MHC. A combination of conserved and locusspecific primers was used to amplify horse MHC class I genes with classical and non-classical characteristics. Multiple clones from each haplotype identified three to five classical sequences per homozygous animal, and two to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 57 publications
(85 reference statements)
2
65
0
Order By: Relevance
“…Equine MHC class I allele (Eqca)-N*00602 (formerly designated as the equine MHC I 7-6 allele) is associated with the serologically defined ELA-A1 alleles (19,(23)(24)(25), which are prevalent in the Arabian horse and mixed-breed pony. Another ELA allele, Eqca-N*00601, formerly designated as the equine MHC I 114 allele, which differs from Eqca-N*00602 allele by a single amino acid (E152V) within the peptide-binding groove (20,25), resulted in the abrogation of epitope peptide Gag-GW12-specific CTL recognition even though Gag-GW12 can still bind to Eqca-N*00601 (20). This phenomenon highlights the immunologic importance of MHC I polymorphism for antiviral immunity.…”
mentioning
confidence: 99%
“…Equine MHC class I allele (Eqca)-N*00602 (formerly designated as the equine MHC I 7-6 allele) is associated with the serologically defined ELA-A1 alleles (19,(23)(24)(25), which are prevalent in the Arabian horse and mixed-breed pony. Another ELA allele, Eqca-N*00601, formerly designated as the equine MHC I 114 allele, which differs from Eqca-N*00602 allele by a single amino acid (E152V) within the peptide-binding groove (20,25), resulted in the abrogation of epitope peptide Gag-GW12-specific CTL recognition even though Gag-GW12 can still bind to Eqca-N*00601 (20). This phenomenon highlights the immunologic importance of MHC I polymorphism for antiviral immunity.…”
mentioning
confidence: 99%
“…Equine MHC Class I with Threonine at Position 173 Is Unable to Act as an EHV-1 Receptor-Some equine MHC class I genes reportedly have valine, glutamic acid, or threonine instead of alanine at the position corresponding to position 173 of A68 (16). Among the equine MHC class I nucleotide sequences registered in GenBank, we successfully obtained the equine MHC class I clone 3.4 cDNA, which has a threonine residue at position 173, from primary equine cells by RT-PCR (Fig.…”
Section: Hydrophobicity Of the Amino Acid At Residue 173 In Equine Mhmentioning
confidence: 99%
“…MHC class I is polygenic and polymorphic (15). Fifty equine MHC class I genes were identified among 10 different serologically defined equine MHC class I haplotypes (16), and seven MHC class I loci were transcribed in an MHC homozygous individual (17). Although previous studies have shown that three equine MHC class I molecules can act as EHV-1 receptors (13,14), it is unclear whether all MHC class I molecules are involved in EHV-1 infection.…”
mentioning
confidence: 99%
“…Antczak, personal communication). The genes from which the alleles originated had previously been assigned to four MHC class I loci (Supplementary File 3; see (Tallmadge et al, 2010) for nomenclature). To capture any additional alleles, generic RT-PCR primers were also used (adapted from (Chung et al, 2003)) that closely matched homologous regions of all the classical MHC class I genes but did not bind to known non-classical and pseudogene sequences.…”
Section: Rt-pcrs For Mhc Class I Genotypingmentioning
confidence: 99%
“…Equine MHC class I genes and primers used to amplify specific alleles by RT-PCR. Tallmadge et al (2010).^primers adapted from Chung et al (2003) N/A = not applicable…”
Section: 1(b2)mentioning
confidence: 99%